Strategies to improve safety profile of AAV vectors - Suoranta, Tuisku; Laham-Karam, Nihay; Ylä-Herttuala, Seppo (Frontiers in Molecular Medicine, 2022)
Adeno-associated virus (AAV) vectors are currently used in three approved gene therapies for Leber congenital amaurosis (Luxturna), spinal muscular atrophy (Zolgensma) and Haemophilia A (Roctavian), with several more therapies being investigated in clinical trials. AAV gene therapy has long been considered extremely safe both in the context of immunotoxicity and genotoxicity, but recent tragic deaths in the clinical trials for X-linked myotubular myopathy and Duchenne’s muscular dystrophy, together with increasing reports of potential hepatic oncogenicity in animal models have prompted re-evaluation of how much trust we can place on the safety of AAV gene therapy, especially at high doses. In this review we cover genome and capsid engineering strategies that can be used to improve safety of the next generation AAV vectors both in the context of immunogenicity and genotoxicity and discuss the gaps that need filling in our current knowledge about AAV vectors.